Synthesis and Biological Evaluation of Novel Chromone+Donepezil Hybrids for Alzheimer's Disease Therapy - Malek, Rim; Refouvelet, Bernard; Benchekroun, Mohamed; Iriepa, Isabel; Moraleda, Ignacio; Andrys, Rudolf; Musilek, Kamil; Marco-Contelles, José; Ismaili, Lhassane (Current Alzheimer research, 2019)
BACKGROUND: Many factors are involved in Alzheimer's Disease (AD) such as amyloid plaques, neurofibrillary tangles, cholinergic deficit and oxidative stress. To counter the complexity of the disease the new approach for drug development is to create a single molecule able to act simultaneously on different targets. OBJECTIVE: We conceived eight drug likeliness compounds targeting the inhibition of cholinesterases and the scavenging of radicals. METHODS: We synthesised the new molecules by the Passerini multicomponent reaction and evaluated their inhibitory activities against acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) as well as their antioxidant activities by the Oxygen Radical Absorbance Capacity (ORAC) assay. The lipinski's rule for drug likeness and in silico ADME prediction was also performed. RESULTS: Compounds 4f [IC50 (EeAChE) = 0.30 μM; IC50 (eqBuChE) = 0.09 μM; ORAC = 0.64 TE] and 4h [IC50 (EeAChE) = 1 μM; IC50 (eqBuChE) = 0.03 μM; ORAC = 0.50 TE] were identified as hits for further development. CONCLUSION: The Passerini reaction allowed us the facile synthesis of ditarget molecules of interest for the treatment of AD.
Keywords: Drug Evaluation, Preclinical; Acetylcholinesterase; Donepezil; cholinesterasové inhibitory; preklinické hodnocení léčiv; lidé; Free Radical Scavengers; Chromones; donepezil; Butyrylcholinesterase; acetylcholinesterasa; Alzheimerova nemoc; Humans; Cholinesterase Inhibitors; butyrylcholinesterasa; chromony; Alzheimer Disease; scavengery volných radikálů